EVALUASI PEJANTAN FRIES HOLLAND DENGAN METODE CONTEMPORARY COMPARISON DAN BEST LINEAR UNBIASED PREDICTION - Wahyu Setyaningsih, Dwi (JURNAL AGRI-TEK, 2017)
Progeny test a study was carried out on five Holstein Friesian Bulls at Artificial Insemination Centre Singosari Malang. The study was based on 234 milk production records of daughter cows. The progeny test was done based on contemporary comparison (CC) and Best Linear Unbiased Prediction (BLUP) methods. The result analysis showed that CC values of D, A, B, F and E bulls were 194,754 kg, 132,321 kg, 108,084 kg, -126,747 kg and -338,985 kg respectively. Therefore Best Linear Unbiased Prediction (BLUP) values of B, B, A, F and E bulls were 93,5 kg, 81,9 kg, -9,1 kg, -67,3 kg and -99,0 kg respectively. There was no significant Spearman’s rank correlation between the CC method and BLUP method. According to the superiority of these methods, it was known that the CC method was still a reliable method for progeny test.Keywords : progeny test, zuriat contemporary comparison, best linear unbiased